Pemecahan Sertifikat (Splitzing) Tanah Kavling di Kantor Notaris & PPAT - Nadia Hera Aurelia; Kamilia Sari; Achmad Rion (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Splitzing a plot of land is the process of dividing a piece of land into several parts. In the implementation of the process, the master certificate of the land will be turned off, and then a new certificate will be issued with an amount according to the results of the land parcel division. This study aims to analyze and compare the procedures for solving land certificates that were previously valid with those that are currently in force. This study identifies significant changes in the requirements, stages, and time required in the process of breaking the certificate. In this study, the author uses a normative juridical method, namely a study that examines the Process of Splitting Certificates of Residential Land Plots in general. The techniques used for data collection are documentation studies by collecting literature materials and interview techniques. The process of breaking the land right certificate can be carried out by submitting an application for the separation of land rights that are separated or divided into several parts, mentioned in Article 49 paragraph (1) of Government Regulation No. 24 of 1997 concerning Land Registration and in Article 49 paragraph (2) of Government Regulation No. 24 of 1997 concerning Land Registration. Regarding the breakdown of the master certificate, it is known that the legal basis for the breakdown of the land right certificate refers to the provisions of article 48 of Government Regulation Number 24 of 1997. Land Deed Making Officials (PPAT) are public officials who are authorized to make authentic deeds regarding certain legal acts regarding land rights or property rights over flats contained in Article 1 of Government Regulation Number 24 of 2016 concerning Amendments to Government Regulation Number 37 Number 1997 concerning Regulations on the Position of Land Deed Making Officials.